Interaction between Road Network Connectivity and Spatial Pattern. (2016) - Sreelekha, M.G.; Krishnamurthy, K.; Anjaneyulu, M.V.L.R.
Abstract: Road network is considered to be one of the keys to regional development of a region. The huge developmental cost of the road network demands effective utilisation, which can be attained only when there is proper connectivity and orientation. But the road network in many urban areas develop in an organic growth pattern. Hence a great emphasis needs to be given to the connectivity pattern of the road network. Urban road network has less theoretical research. Only some developed countries have carried out the evaluation of urban road network and hence it has great potential for development and application prospects. In this study an attempt has been made to analyse the road network connectivity and spatial pattern existing in Calicut city in India, and hence to determine if the network connectivity can explain significant variance in the spatial pattern of the network structure. Analysis reveals that transport network fractality is directly varying with respect to connectivity and coverage of the study area. Network density could better predict fractality of the road network than any other connectivity indicators. This means that there is significant relationship between the level of road network development and the network spatial structure within the study area.